Reconceptualizing Audit Quality in the Digital Era: A Systematic Literature Review of Key Audit Matters, Digital Transformation, and Emerging Audit Practices - Basri, Husen; Widyastuti, Tri; Kuntadi, Cris; Harnovinsah, Harnovinsah (LPPM Universitas Jambi, 2026)
Recent technological advances have significantly transformed audit processes and challenged traditional notions of audit quality. This study integrates these areas by analyzing audit quality in digital environments through technological, institutional, and communication lenses. To investigate these interconnected topics, this study used a Systematic Literature Review (SLR) based on the PRISMA 2020 framework and the Theory–Context–Characteristics–Methodology (TCCM) approach. A search of the Scopus database returned 511 records initially. After identification, screening, eligibility checks, and inclusion, 53 articles were selected for qualitative synthesis and thematic analysis.Building on this review, the results show that research on audit quality is changing in important ways.. Digital technologies such as artificial intelligence, big data analytics, and digital audit systems affect not only how audits are conducted but also how information is shared and how institutions operate. The review also finds that digital transformation, governance, KAM disclosure, and audit communication are increasingly interconnected. Still, the field is fragmented, especially in theory and research methods. There is also a heavy focus on quantitative methods, and audit quality often depends on the specific institutional context. In light of these findings, this review offers a new perspective on audit quality, viewing it as a complex concept shaped by both technology and institutions. Future research could draw on broader theoretical frameworks and a mix of methods to better understand the challenges of auditing in digital settings.